2016
DOI: 10.1073/pnas.1516648113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adolescent marijuana use on intelligence: Results from two longitudinal twin studies

Abstract: Marijuana is one of the most commonly used drugs in the United States, and use during adolescence-when the brain is still developing-has been proposed as a cause of poorer neurocognitive outcome. Nonetheless, research on this topic is scarce and often shows conflicting results, with some studies showing detrimental effects of marijuana use on cognitive functioning and others showing no significant long-term effects. The purpose of the present study was to examine the associations of marijuana use with changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 50 publications
10
138
0
3
Order By: Relevance
“…However, this study was limited in terms of controlling for confounds and a relatively small number of the total study population in the affected group. Two recent large scale follow-up studies have found that cannabis use is not associated with reduced IQ when controlling for additional confounders and genetic factors 54,55 . These latter studies only followed participants up to the ages of 15 and 20 years and do not exclude the possibility that IQ might be affected if cannabis use and/or dependence is maintained for longer.…”
Section: Cognition and Intelligencementioning
confidence: 99%
“…However, this study was limited in terms of controlling for confounds and a relatively small number of the total study population in the affected group. Two recent large scale follow-up studies have found that cannabis use is not associated with reduced IQ when controlling for additional confounders and genetic factors 54,55 . These latter studies only followed participants up to the ages of 15 and 20 years and do not exclude the possibility that IQ might be affected if cannabis use and/or dependence is maintained for longer.…”
Section: Cognition and Intelligencementioning
confidence: 99%
“…These findings have been criticized as potentially representing a regression to the mean, given that the marijuana-using cohort had higher baseline IQ than the non-marijuana-using cohort. A recent longitudinal twin study found that IQ deficits observed in marijuana users may be attributable to confounding factors like familial and environmental influences rather than the direct neurotoxic effect of marijuana [55]. Of note, these studies examined a small number of IQ subtests and did not assess other measures of executive function or working memory that have been found to be affected by heavy marijuana use.…”
Section: Neural Features That Follow Adolescent Substance Usementioning
confidence: 99%
“…The latter includes genes and shared environment [25], socioeconomic status [26, 27] and childhood problems, including mental illness, cognitive difficulties and lower academic achievement preceding SUD [28-32]. Also, several of these environmental and constitutional factors have been associated with early school leaving [33, 34].…”
Section: Introductionmentioning
confidence: 99%